Investments for Carbon Footprint Reduction: An Instructional Case - Marc Wouters; Niklas Letmathe (Accounting Perspectives, 2025)
This instructional case explores strategic decision-making at CarCompany (CarCo), a large automaker that is transitioning to battery electric vehicles. CarCo aims to reduce the carbon dioxide (CO2) emissions at their own sites and at suppliers' sites. The challenge is to select a group of CO2 reduction initiatives that achieves the objectives set by CarCo's management while staying within budgetary restrictions. Another challenge is renegotiating some CO2 reduction initiatives with suppliers so that greater overall CO2 reductions can be achieved. Finally, decentralization of objectives and budgets for CO2 reductions needs to be considered. CarCo's Sustainability Manager, Julia Neumann, has been asked to select from the list of proposed projects and present her recommendations to CarCo's board. In this case, students need to apply rigorous analyses on the basis of cost-benefit analysis, justify their decisions, and think outside the box. They are asked to assess how existing evaluation techniques can be used and adapted to CO2 emissions. The case delves into the complexities of the transition to cleaner production processes and the expanding network of suppliers, employees, and other stakeholders that need to be involved in the process.
Keywords: 650; carbon footprint reduction; cost-effectiveness analysis; environmental management accounting; investment project selection; sustainability